[PP.29.21] IMPAIRED HEART RATE VARIATION WHEN STANDING: A SIMPLE MARKER OF EARLY VASCULAR AGING AND AUTONOMIC DYSFUNCTION. (September 2017) - Gonzalez, S.; Kempny, P.; Svane, J. Chiabaut; Castellaro, C.; Schiavone, M.; Inserra, F.; Hita, A.
Abstract : Objective: a- To evaluate associations between heart rate variation when standing (HRVS) and vascular stiffness in hypertensives and normotensives. b-To determine independent predictors of impaired HRVS (I-HRVS) in these populations. Design and method: 396 consecutive subjects who attended to the Champagnat Cardiometabolic Center of Austral Hospital were evaluated. The exclusion criteria were: age below 18/above 80 years, secondary hypertension, heart disease, anaemia, diabetes, sympatholitics, and chronotropic drugs. HR, BP (OMROM HEM-781CPINT) and PWV (Mobil-O-Graph, IEE) were measured in supine position after 5 minute rest, and HR was determined again then of 3 minutes of standing position. HRVS was calculated between standing and supine positions. PWV was evaluated according to sextiles of HRVS in hypertensive and normotensive patients (ANOVA, Student Newman Keuls). I-HRVS was defined as those HRVS values contained in the first sextile (lower HRVS). Independent predictors of l-HRVS, adjusted for age, sex, BP, anthropometric factors and medications, were determined. (MEDCALC v12.5.0.0). Results: 314 patients were included: 162 treated hypertensives (54.7 ± 10.6 years, 134 ± 19/86 ± 13 mm Hg, 58.0% males) and 152 normotensives (47.7 ± 10.2 years, 119 ± 10/77 ± 8 mm Hg, 41.4% males). PWV presented a negative relationship across sextiles of HRVS in hypertensives (p = 0.03) and normotensives (p = 0.01). l-HRVS resulted below 2 beats in hypertensives and below 5 beats in normotensives. In univariate analysis, supine HR, sex, PWV and calcium channel blockers were different according to sextiles of HRVS in hypertensives. Supine HR and PWV were also different among sextiles of HRVS in normotensives. In logistic regressions, only supine HR and PWV were independent predictors of I-HRVS in hypertensives (HR: p = 0.0009, and PWV: p = 0.03) and normotensives (HR: p = 0.0002, and PWV: p = 0.03). Figure. No caption available. Conclusions: Across the broad spectrum of BP, I-HRVS was related independently with increased arterial stiffness and higher basal HR. This findings may be explained through a lower baroreceptor functioning secondary to vascular stiffness, as a cause of the lesser parasympathetic cardiac control observed in this subjects. Thus, I-HRVS would be a simple marker of early vascular aging and autonomic dysfunction both in normotensive and hypertensive patients.